New Concepts in Inflammatory Bowel Disease - Mutar Mahdi, Batool (IntechOpen, 2018)
Inflammatory bowel disease is a chronic immune-mediated inflammation of the gastrointestinal tract of unknown origin, which includes Crohn's disease, ulcerative colitis, and inflammatory bowel disease of unclassified type. It is associated with different intestinal and extraintestinal manifestations like different neurological and psychiatric disorders. Histology is an important tool in the diagnosis and prognosis of inflammatory bowel disease and has an increasing part in patients' management. The objective of treatment is to make and keep long-lasting remission by immunosuppressive treatment like corticosteroids, thiopurines, and monoclonal antibodies directed against tumor necrosis factor alpha. Therapeutic drug monitoring of thiopurines by measuring levels of their metabolites has been proposed as a potentially effective tool in optimizing therapy in inflammatory bowel disease. Diets and their components influence microbiota of the intestine, function of the epithelial barrier, immune response, and other factors that have an important role in development and treatment of inflammation in the gut mucosa.